Anti-inflammatory properties of bergenin in mice - Guilherme A. L. Oliveira, Andreza K. S. Araujo, Gabriella Pacheco, Ana P. Oliveira, Jelson L. Carvalho, Letícia S. Chaves, Gabrielle C. Sousa, André L. F. Lopes, Priscila C. Silva, Ana Carolina M. Leódido, Kerolayne M. Nogueira, Luan K. M. Souza, Thiago L. Araújo, Lucas A. D. Nicolau, Jand Venes R. Medeiros (Journal of Applied Pharmaceutical Science, 2019)
Inflammation is a protective biological reaction against infection and has undesirable effects. Although bergenin (BG), a C-glycoside derivative of 4-O-methyl gallic acid, has many pharmacological properties, no study has demonstrated the activity of BG in inflammatory mediators, such as histamine and prostaglandin E2 (PGE2). The present study investigated the anti-inflammatory activity of BG obtained from Peltophorum dubium Taub, in edema models induced by carrageenan and inflammatory mediators in Swiss mice. The assessment of its toxicity was also conducted. The evaluations of this study indicated that the pre-treatment with BG (25 mg/kg) significantly reduced edema induced by carrageenan, compound 48/80, histamine, and PGE2 (p < 0.05). Also, pre-treatment with BG inhibited the recruitment of leukocytes and neutrophils, reducing adhesion and rolling of these cells, myeloperoxidase (MPO) activity, malondialdehyde (MDA) levels, and vascular permeability. Treatment with BG (2,000 mg/kg) showed no toxic signs in hippocratic screening, weight of animals, water and feed intake, vital organs weight and histopathological evaluation, and hematological and biochemical parameters. In conclusion, these results show that the BG obtained from P. dubium Taub has anti-inflammatory activity against different models of inflammation, reducing neutrophil migration and damage caused by oxidative stress and lipid peroxidation. BG did not present toxic effects in the evaluated parameters.
Keywords: Inflammation, edema, flavonoids, toxicity.